Pengaruh Lingkungan Kerja Terhadap Komitmen Organisasional Pegawai Kantor Badan Kepegawaiandan Pengembangan Sumber Daya Manusia Kabupaten Luwu Utara - Nursia Bala; Tenri S.P Dipoatmodjo; Andi Mustika Amin; Chalid Imran Musa; M.Ikhwan Maulana Haeruddin (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This research is to find out whether there is an influence of the work environment on organizational commitment at the BKPSDM Office in North Luwu Regency. This research is quantitative research with a descriptive approach and is population research. The sample in this research was all employees at the BKPSDM Office in North Luwu Regency 47 people. The hypothesis test in this research used a multiple linear regression test and obtained the results, namely: Based on the results of the hypothesis test using a multiple linear regression analysis test, it shows that physical work environment and non-physical work environment variables simultaneously influence organizational commitment at the BKPSDM Office in North Luwu Regency. The results of the hypothesis test also show that the physical work environment partially influences organizational commitment at the BKPSDM Office in North Luwu Regency and the non-physical work environment partially influences organizational commitment at the BKPSD Office in North Luwu Regency.